MARTIROLOGI - Edison R.L. Tinambunan (Studia Philosophica et Theologica, 2015)
One period of Father of the Church was martyrdom which had begun since Apostle’s time up to empire Constantine. During these four centuries, many Christians were suffering and condemned to death. This period was one of the darkness of the history of the Church. The other side, this difficult time had created the theology of martyrdom in the Church, which lasts to present time. This article gives various aspects of martyrdom of the Father of the Church.